1990
DOI: 10.1620/tjem.161.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ampicillin, cefmetazole and minocycline on the adherence of Branhamella catarrhalis to pharyngeal epithelial cells.

Abstract: of Ampicillin, Cefmetazole and Minocycline on the Adherence of Branhamella catarrhalis to Pharyngeal Epithelial Cells. Tohoku J. Exp. Med., 1990, 161(1),1-7Using pharyngeal epithelial cells from a healthy adult and eight strains of Branhamella catarrhalis (B. catarrhalis) isolated from eight patients with respiratory infection the effect of subminimal inhibitory concentrations of cefmetazole, ampicillin and minocycline on adherence was examined. Cefmetazole-treated bacterial attachment (44 + 28; mean ± s.D.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Evidence has shown that respiratory pathogens first attach to the pharyngeal cells, then according to its virulence, tissue tropism and host resistance, causes different types of respiratory injections. Several important events of adherence of B. catarrhalis have been reported from our department (1,12,15,16) with the aim to identifying the adhesin and receptor.…”
mentioning
confidence: 99%
“…Evidence has shown that respiratory pathogens first attach to the pharyngeal cells, then according to its virulence, tissue tropism and host resistance, causes different types of respiratory injections. Several important events of adherence of B. catarrhalis have been reported from our department (1,12,15,16) with the aim to identifying the adhesin and receptor.…”
mentioning
confidence: 99%
“…Subsequently we reported various important aspect of this bacteria to elucidate its mechanism of pathogenicity (Ahmed et al, 1990; Rikitomi et at., 1991; Ahmed et al, 1992). In this study we found in Mae Sot, Thailand, B. catarrhalis is one of the major pathogen in respiratory infection.…”
Section: Discussionmentioning
confidence: 99%